Sacred claims and the politics of indigeneity in Australia - Johnson, Miranda ca. 20./21. Jh. (Journal of religious and political practice, 2018)
The claims of Indigenous peoples to sacred sites have generated far-reaching debates about identity, authenticity, and history in Australia in recent decades. This is surprising in such an avowedly secular country, where there is no constitutional or statutory recognition of principles of religious freedom. This article charts the emergence of sacred claims and their imbrication with a broader politics of indigeneity in the 1970s. These claims shaped and were reshaped by state law, sometimes holding out the possibility of the restitution not only of land but also of culture and identity for Indigenous peoples. As these claims and the broader politics of indigeneity to which they were attached came to challenge the settler state, its history and moral foundations, as well as economic development, both the content of claims and the characters of the claimants became subject to sharp critique.